Guido Bonarelli, tireless explorer and geologist: Pioneer in the prospection of hydrocarbons in Argentina - Concheyro, A. (2011)
Guido bonarelli is an important figure in the field of geology in Argentina and he constituted one of the most relevant geologists in the oil exploration in our country. of Italian origin, he was born in Ancona on July 25, 1871 and he died in montereano, January 11, 1951. He excelled in stratigraphy, geological survey, historical geology and paleontology, becoming a specialist in the taxonomy of Jurassic ammonites and the stratigraphy of the Central Apennines. His professional work began in Italy and continued in southeast Asia, south America, bolivia, Chile, Argentina and uruguay. During 1911-1918, he worked in the Dirección General de minas, Geología e Hidrografía of Argentina. He defined the sub-Andean ranges as an orographic complex and he pointed out the locations of oil and natural gas reservoirs. He developed his researches in several Argentinean provinces and in the pacific Chilean coast. During his second period of research in Argentina (1923 -1927), Guido bonarelli organized the Geological Division of YpF, and he intensified the oil exploration in the northwestern of Argentina, as well as in the provinces of mendoza, neuquén and the Comodoro rivadavia region. He developed a professional and academic team that dealt with the geology and the hydrocarbon exploration in the country. bonarelli discovered in 1891 a sedimentary horizon that has great importance and it serves as a baseline to characterize the global anoxic event known to the Cenomanian-turonian transition. this world-famous skyline has been named Livello Bonarelli as a posthumous tribute to his discoverer.